Porous Polymer Membranes by Hard Templating – A Review. Issue 1 (28th September 2017) - Stucki, Mario; Loepfe, Michael; Stark, Wendelin J.
Abstract : Membranes are designed to bridge a precise separation process at the nanoscale with industrial applications running at cubic meters per hour. This review outlines materials applied in membrane production with a particular focus on polymers. Membrane performance and created value are directly linked to controlled pore formation. Their economic relevance has created a number of large companies and associated academic research at top institutions. The authors review, therefore, starts from well‐established techniques applied in products and then moves on to evolving concepts from academia. Pore formation through hard templating is a versatile field for separation processes. A more detailed view is given on the two known concepts for nanopore formation, namely colloidal templates and random hard salt templating. A comparison between these two concepts underlines their relevance to combine a process specific separation with large scale manufacturing requirements (i.e., upscale possibility, flexible process control and environmental impact). Abstract : Membranes bridge nanoscale separation with high volume throughput. The development of membranes has resulted in a large variety of materials used for porous separators. This article introduces the relevant membrane processes and focuses on porous polymer membranes. Its main body explains sacrificial hard templating. Ordered colloidal crystals are compared to random templates with respect to their scalability and application.